Metals for biomedical devices - Niinomi, M. (Woodhead Publishing series in biomaterials., 2019)
Metals for Biomedical Devices, Second Edition, has been fully updated and builds upon the success of its first edition, discussing the latest techniques in metal processing methods and the behavior of this important material. Initial chapters review the current status and selection of metals for biomedical devices. Subsequent chapters cover mechanical behavior, degradation and testing, corrosion, wear testing and biocompatibility, the processing of metals for biomedical applications, including topics such as forging metals and alloys, surface treatment, coatings and sterilization. Chapters in the final section discuss the clinical applications of metals, such as cardiovascular, orthopedic and new generation biomaterials. With its distinguished editor and team of expert contributors, this book is a standard reference for materials scientists, researchers and engineers working in the medical devices industry and academia.